Når fårene forlader flokken. En religionssociologisk analyse af udmeldelser fra folkekirken - Lüchau, Peter (Religionsvidenskabeligt Tidsskrift, 2015)
ENGLISH SUMMARY: Membership of the Danish National Church has declined steadily but has not until now been the subject of sociological analysis. Using data from governmental databases housed at Statistics Denmark the article analyze individuals who disaffiliated from the Danish National Church from 2003 to 2007. Secularization theory is used as the starting point for the analysis. Individuals who disaffiliated were generally younger, more affluent, more educated, more urbanized and more often living with non-members than the rest of the population. Age differences between the disaffiliated and the rest of the population suggested that disaffiliation was the result of a life-cycle effect rather than a generational effect. It was also shown that non-members tended not to baptize their children while members did. Therefore it must be concluded that the declining membership of the Danish National Church is the result of a general societal development. DANSK RESUME: Artiklen analyserer ved hjælp af registerdata fra Danmarks Statistik individer som har meldt sig ud af folkekirken i perioden 2003 til 2007. Med udgangspunkt i sekulariseringsteori må det forventes, at de udmeldte var yngre, mere velhavende, højere uddannede og mere urbaniserede end resten af befolkningen. Analysen af data bekræfter forventningen med visse forbehold. De udmeldte var mere velhavende, højere uddannede og mere urbaniserede end resten af befolkningen. De var også generelt yngre; men de udmeldtes aldersprofil antyder, at udmeldelse var et livscyklus fænomen og ikke et generationsfænomen som teorien forventede. Det kunne også konstateres, at medlemskab af folkekirken og mangel på samme videreførtes fra forældre til børn. Resultaterne antyder, at folkekirkens dalende medlemstal er resultatet af en generel samfundsudvikling.